2014
DOI: 10.1089/cmb.2013.0134
|View full text |Cite
|
Sign up to set email alerts
|

Exactly Computing the Parsimony Scores on Phylogenetic Networks Using Dynamic Programming

Abstract: Scoring a given phylogenetic network is the first step that is required in searching for the best evolutionary framework for a given dataset. Using the principle of maximum parsimony, we can score phylogenetic networks based on the minimum number of state changes across a subset of edges of the network for each character that are required for a given set of characters to realize the input states at the leaves of the networks. Two such subsets of edges of networks are interesting in light of studying evolutiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Spanning trees are subsets of graphs that cover all nodes without any loop ( Stam, 2014 ; Tewarie et al, 2015 ). The MST is the tree with the lowest total cost ( Graham and Hell, 1985 ); the unique, unweighted, binary graph that is made by the shortest path between all pairs of nodes without the occurrence of a loop. Therefore, the minimum connectivity cost involved in spanning all nodes is recovered by MST analysis ( Tewarie et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Spanning trees are subsets of graphs that cover all nodes without any loop ( Stam, 2014 ; Tewarie et al, 2015 ). The MST is the tree with the lowest total cost ( Graham and Hell, 1985 ); the unique, unweighted, binary graph that is made by the shortest path between all pairs of nodes without the occurrence of a loop. Therefore, the minimum connectivity cost involved in spanning all nodes is recovered by MST analysis ( Tewarie et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…We remain open to the hypothesis that hybridization has contributed to the lack of deep phylogenetic resolution and of distinct morphological characters that are useful for taxonomic purposes. Using a manageable subset of our data to develop a parsimony network analysis, it was found that certain species were best explained as the direct results of reticulate events (the joining of lineages through time) in the most parsimonious network (Kannan and Wheeler, ), and we recommend expanding this line of investigation with Camponotus going forward.…”
Section: Discussionmentioning
confidence: 99%
“…Hardwired costs on the other hand ( H ( N , C ) score ) do not depend on display trees, but are the sum of the weights of all edges ( e ) in the network N , where the edge weights ( w ( e )) are the minimum number of character changes between vertex states that bound each edge [ 21 , 22 ]. …”
Section: Trees and Networkmentioning
confidence: 99%